2019
DOI: 10.3390/ma12101719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Baghdadite Substitution on the Physicochemical Properties of Brushite Cements

Abstract: Brushite cements have been clinically used for irregular bone defect filling applications, and various strategies have been previously reported to modify and improve their physicochemical properties such as strength and injectability. However, strategies to address other limitations of brushite cements such as low radiopacity or acidity without negatively impacting mechanical strength have not yet been reported. In this study, we report the effect of substituting the beta-tricalcium phosphate reactant in brush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…First is the ability of Baghdadite to maintain a physical pH value of 7.3 in an extracellular solution . Extracellular pH plays a key role in the initiation of cellular senescence, and the maintenance of physiological pH conditions by Baghdadite might be able to correct the aged tissue-fostered inflammatory and acidic environment that promotes dysfunctional mitochondria and cellular senescence. , Second, the profile of ions (e.g., calcium and silicon) released by the Baghdadite material into the surrounding environment is distinct from that of HA/TCP. , Different ion conditions in the extracellular microenvironment can lead to significant changes in the ion channels present in the cellular membrane, which are implicated in modulating cellular senescence. , A recent study showed that there are regenerative and protective effects of ion extracts from calcium silicate on senescent fibroblasts induced by high glucose . It would be of great interest to gain further insight into how the soluble chemical environment, including ions and pH, modulate mitochondrial function and cellular senescence and ultimately contribute to tissue regeneration in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First is the ability of Baghdadite to maintain a physical pH value of 7.3 in an extracellular solution . Extracellular pH plays a key role in the initiation of cellular senescence, and the maintenance of physiological pH conditions by Baghdadite might be able to correct the aged tissue-fostered inflammatory and acidic environment that promotes dysfunctional mitochondria and cellular senescence. , Second, the profile of ions (e.g., calcium and silicon) released by the Baghdadite material into the surrounding environment is distinct from that of HA/TCP. , Different ion conditions in the extracellular microenvironment can lead to significant changes in the ion channels present in the cellular membrane, which are implicated in modulating cellular senescence. , A recent study showed that there are regenerative and protective effects of ion extracts from calcium silicate on senescent fibroblasts induced by high glucose . It would be of great interest to gain further insight into how the soluble chemical environment, including ions and pH, modulate mitochondrial function and cellular senescence and ultimately contribute to tissue regeneration in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the microenvironment around oligodendrocyte progenitor cells stiffens with age and softening their substrate restores the function of these aged progenitor cells . The bone extracellular matrix structure and chemical composition are altered during the ageing process, , with a steady and significant decrease in bone mechanical properties and density. In addition, other factors in the bone microenvironment also change with aging, including the age-related metabolic acidosis that plays an important role in the pathogenesis of the degenerative diseases of aging and loss of bone tissue. , We have developed a novel bioactive ceramic (Baghdadite, Ca 3 ZrSi 2 O 9 ) with improved mechanical properties, excellent biocompatibility, and bone regenerative capacity, in comparison to the clinically used bone graft substitute, hydroxyapatite (HA)/β-tricalcium phosphate (β-TCP). Baghdadite also holds a unique ability to maintain simulated body fluid at a physiological pH of 7.3–7.5 . In this study, we hypothesized that Baghdadite scaffolds will foster an anti-senescent microenvironment to modulate the functionally compromised senescent bone cells and restore the in vivo impaired bone repair and regenerative capacity in old rats.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, bone repair scaffolds are required to possess high radiopacity for noninvasively tracking and imaging the filling effect in clinical operations, in vivo degradation, and new bone growth by X-ray-based techniques, such as fluoroscopy, computer tomography, and radiography [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. However, the intrinsic radiopacity of bone repair scaffolds is usually insufficient, and it is difficult to distinguish them from natural bone tissues.…”
Section: Introductionmentioning
confidence: 99%
“…However, the intrinsic radiopacity of bone repair scaffolds is usually insufficient, and it is difficult to distinguish them from natural bone tissues. For enhancing their radiopacity, X-ray contrast agents such as Ba-based [ 22 , 23 ], Zr-based [ 24 , 25 , 26 ], Bi-based [ 27 , 28 , 29 ], and Sr-based [ 30 , 31 , 32 ] compounds are added into them to construct the composite scaffolds. Although BaSO 4 and ZrO 2 are widely used in poly (methyl methacrylate) (PMMA) bone cements as the radiopacifier, there are potential physical, mechanical, and biological risks if the particles are released from the scaffolds as they are unabsorbable in the physiological environment [ 22 , 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…CPC always consists of two phases, -solid particles and liquid, which, upon mixture with each other, form a moldable paste to fill the complex bone defect site and then undergo a hydration reaction, resulting in a strong material–bone interface [ 2 , 3 ]. The final cement product is hydroxyapatite (HA) or brushite phase, which resembles the inorganic components of human bone and thus provides a high level of biocompatibility and osteoconductivity [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%